Evaluasi dari metode: trapesium, simpson 1/3, simpson 3/8 dan newton cotes orde 4-10 untuk menghitung integral tertentu secara numerik - Mulyono Mulyono (Universitas PGRI Semarang, 2022)
Certain integrals are integrals that handle integral computations between predetermined integral boundaries. This study aims to evaluate and compare several methods to calculate certain integrals numerically, especially for quite complex and tabulated functions, namely the function f(x), which is not explicitly known. The methods in question include the Trapezoidal method, the Simpson 1/3 method, the Simpson 3/8 method, and the Newton-Cotes method of orders 4 to 10. The main factor in comparing the methods mentioned above is the accuracy of the numerical solution. This study shows that for integral problems that can be calculated analytically, the results of calculations using the Newton-Cotes method of order 6 and with many partitions of 12 ( n = 12), the error is 0.0000026%. In contrast, with the Newton-Cotes method of order 6 and with n = 30, the error is 0.000000002 %, while with the Newton-Cotes method of order 10 and using n = 30, the error is 0.00000000 %.